THE EFFECT OF THE IMPLEMENTATION OF MORAL CORE VALUES ON THE WORK MOTIVATION OF ASN SECRETARIAT DPRK PIDIE JAYA REGENCY - Maulida; Dicky Wahyudi; Hendra (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to determine the effect of the implementation of Core Values BerAKHLAK on the work motivation of State Civil Apparatus (ASN) in the Secretariat of the Regional House of Representatives (SETWAN) of Pidie Jaya Regency. The implementation of organizational values is important to improve employee motivation and performance in public institutions. This research used a quantitative approach with a survey method. The population in this study consisted of all ASN and non-ASN employees at the Secretariat of DPRK Pidie Jaya, totaling 67 employees, and the entire population was used as the research sample. Data were collected through questionnaires using a Likert scale and analyzed using statistical methods with the help of SPSS 25.0 software. The results of the study indicate that the implementation of Core Values BerAKHLAK has a positive and significant effect on the work motivation of ASN at the Secretariat of DPRK Pidie Jaya. This is proven by the results of the t-test which show a significance value of 0.000 < 0.05 and a t-count value greater than the t-table value (5.071 > 1.660). The coefficient of determination (R²) value of 0.685 indicates that 68.5% of the variation in ASN work motivation is influenced by the implementation of Core Values BerAKHLAK, while the remaining 31.5% is influenced by other factors outside this study. Therefore, the implementation of Core Values BerAKHLAK plays an important role in increasing ASN work motivation.